PERAN GURU DALAM PENDEKATAN DEEP LEARNING UNTUK KETERAMPILAN BERPIKIR KRITIS SISWA SDN MADE I SURABAYA - Sasabilla, Devi Amanda; Aditya Khoirun Nisa', Lita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the teacher's role in implementing a deep learning approach to enhance students' critical thinking skills in Grade V mathematics at SDN Made I Surabaya. Employing a qualitative descriptive method, the study involved one teacher and 28 students as subjects. Data were gathered through observation, interviews, and documentation, then analyzed via data reduction, data display, and conclusion drawing. The findings reveal that the teacher functions as a facilitator, mentor, mediator, and motivator within the deep learning framework by presenting contextual problems, posing open-ended questions, and fostering discussion and reflection. This approach effectively develops critical thinking, specifically in problem identification, information analysis, logical reasoning, and drawing conclusions. Challenges such as time constraints and diverse student abilities are addressed through the use of varied instructional media and scaffolded guidance.